PENGARUH MODEL PEMBELAJARAN DAN KEBUGARAN JASMANI TERHADAP SELF REGULATED LEARNING SISWA SMK - Fuad Saadi, - (2023)
ABSTRACT Fuad Saadi 2105104 THE INFLUENCE OF LEARNING MODELS AND PHYSICAL FITNESS ON SELF REGULATED LEARNING OF VOCATIONAL SCHOOL STUDENTS Supervisor Dr. Agus Mahendra, M.A, Prof. Dr. Berliana, M.Pd This research departs from the problem of low self-regulated learning in SMK students. The purpose of this study is to discuss the effect of the Teaching Personal and Social Responsibility (TPSR) learning model and the cooperative learning model and its interaction with physical fitness on self-regulated learning in SMK students. The method used is an experiment with a 2x2 factorial design. The sample in this study were sixty students majoring in mechanical engineering class XI at SMKN 1 Bangkinang. Data analysis used SPSS version 25 with hypothesis testing through two way ANOVA and Tukey test. Based on the calculation and analysis of the data, the following results were obtained: first, overall there were differences between the TPSR and cooperative models towards self-regulated learning where the TPSR learning model was better than cooperative; second, there is an interaction between the learning model and physical fitness which has a different effect on increasing self-regulated learning: third, there is a different effect between the TPSR and cooperative models on self-regulated learning in the high physical fitness group where the TPSR learning model is better; fourth, there is no difference in the effect of the TPSR and cooperative models on self-regulated learning in the low physical fitness group. Because the two learning models do not show different results in the self-regulated learning of vocational students. Keywords : Learning models, physical fitness, and self-regulated learning